Criticism, self-criticism, generative criticism – developing self-awareness and confidence in students of design - Lecanides-Arnott, Mari (South African Journal of Higher Education, 2016)
n the complex field of design, which bridges art and science, designers need to be critically aware and versatile. They should possess breadth and depth of knowledge, skills and understanding that can be transferred and adapted to new and different situations, enabling sustainable and innovative design solutions. Designers need to communicate within a global ‘networked knowledge society’. It has been argued that ‘designers create culture’ and that knowledge and hand skills traditionally required of an artist/designer are essential, as design outcomes are purpose driven and practical. Self-awareness and confidence have been identified as necessary attributes for ‘creative design action’. The role of tertiary design foundation education and in particular an integrated, multidisciplinary design foundation course in the South African context is investigated. In raising students’ critical awareness by instilling an understanding of ‘core ideas’ and the ‘visual language’ specific to the fields of art and design, emphasis is placed on ‘learning to see’ through the act of drawing and the use of colour. Transference from one studio-based subject to another, that takes place through studio group critiques applying comparative analysis as a means of formative assessment, is examined. The iterative nature of the design process in encouraging ‘design thinking’, described as ‘reflection in action’, and which leads to the development of generative self-criticism, is investigated. It is argued that generative self-criticism in students provides an essential benchmarking instrument for the assessment of practical design outputs.